1998
DOI: 10.1095/biolreprod59.6.1464
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Monocyte Chemoattractant Protein-1 in the Bovine Corpus Luteum Around the Time of Natural Luteolysis1

Abstract: Monocyte chemoattractant protein (MCP-1) is a specific chemoattractant for monocytes/macrophages that could have a role in the influx of macrophages into the corpus luteum (CL) during structural luteolysis. In this study, reverse transcription-polymerase chain reaction and in situ hybridization were used to investigate MCP-1 mRNA expression in CL collected from 18 heifers between Days 15 and 20 of the estrous cycle. There was expression of mRNA encoding MCP-1 in luteal tissue from all cows; however, expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 38 publications
1
26
0
Order By: Relevance
“…In the course of follicular atresia and CL involution, chemokine expression and leukocyte infiltration increase [23,[25][26][27][28]. These stages are therefore considered proinflammatory events [24,43,47,48].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the course of follicular atresia and CL involution, chemokine expression and leukocyte infiltration increase [23,[25][26][27][28]. These stages are therefore considered proinflammatory events [24,43,47,48].…”
Section: Discussionmentioning
confidence: 99%
“…While luteal development is accompanied by a dramatic increase in the number of blood vessels, luteal demise is characterized by increased chemokine expression and leukocyte infiltration [23,[25][26][27][28]. PROK1 may therefore assume different roles at different stages of the cycle.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of MCP-1 mRNA or protein in the corpus luteum has been reported for various animal species, including murine [7,12,13], bovine [8,10,14], ovine [8,9], and human [11], but the identity of the cell type(s) responsible for the Mcp-1 gene expression has been ambiguous. In the present study, we have shown that cells expressing MCP-1 mRNA are steroidogenic luteal cells in normally cycling rats.…”
Section: Discussionmentioning
confidence: 99%
“…The reasons for this discrepancy are not certain at present, but they could include 1) the fact that small luteal cells in the sheep express MCP-1, 2) a difference in the conditions of the animals (normal rats vs. prostaglandin F 2␣ -treated sheep), or 3) a difference in the antibodies used to identify steroidogenic cells. Penny et al [10] has raised the possibility that MCP-1 is expressed in CD5-positive T lymphocytes in corpora lutea of the cow; however, their experimental procedure was not accurate enough to identify cell types expressing MCP-1. Penny et al compared two serial luteal sections, one analyzed by in situ hybridization for MCP-1 mRNA and the other by immunohistochemistry with an anti-CD5 antibody.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation